The Role Model Influence on Behavior Transformation in Alexandra Andrews’ Who is Maud Dixon? - Anggun Patma Ayu; Rini Susanti Wulandari (Universitas Negeri Semarang, 2025)
This research presents a Freudian psychoanalytic interpretation of Alexandra Andrews’ Who is Maud Dixon? It focuses on the psychological imbalance projected by the main character, Florence Darrow, as she becomes increasingly obsessed with her role model. Employing a descriptive qualitative design, the study uses the concept of the id, ego and superego to explore the transformation of the ideal-self/desire into obsessive-compulsive disorder and how the obsession for the role model changes the behavior. Initially motivated by the desire of literary achievement, wealth, and fame, her desires escalate into harmful and unethical actions, such as plagiarism and identity theft. The psychological imbalance is characterized by the dominance of the id, the moral disengagement of the ego, and the repression of the superego. It demonstrates a dangerous combination of ambition and obsession. This analysis emphasizes the terrible effects of projecting the ideal-self in the role model, uncovering how the disastrous obsession results in self-disintegration and moral degradation.